2010
DOI: 10.4103/0970-1591.70570
|View full text |Cite
|
Sign up to set email alerts
|

Commonly used intravenous anesthetics decrease bladder contractility: An in vitro study of the effects of propofol, ketamine, and midazolam on the rat bladder

Abstract: Aim:This study was designed to test the hypothesis that propofol, ketamine, and midazolam could alter the contractile activity of detrusor smooth muscle.Materials and Methods:Four detrusor muscle strips isolated from each rat bladder (n = 12) were placed in 4 tissue baths containing Krebs-Henseleit solution. The carbachol (10 −8to 10−4mol/L)-induced contractile responses as well as 5, 10, 20, 30, 40, 50 Hz electrical field stimulation (EFS)-evoked contractile responses of the detrusor muscles were recorded usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Ceran and colleagues evaluated the effects of 3 different intravenous anesthetics: propofol, ketamine, and midazolam on detrusor contractile responses in vitro . Results demonstrated that depressant effects of midazolam on the contractile activity were found to be more significant than ketamine and propofol [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ceran and colleagues evaluated the effects of 3 different intravenous anesthetics: propofol, ketamine, and midazolam on detrusor contractile responses in vitro . Results demonstrated that depressant effects of midazolam on the contractile activity were found to be more significant than ketamine and propofol [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malinovski et al reported from their study investigating the effects of intravenous opioids and ketoprofen on urodynamic parameters in male adults that opioids change urodynamic results in contrast to ketoprofen but the opioid nalbuphine has no effect on detrusor contraction (Malinovsky et al 1998 ). Ceran et al reported that midazolam depressed detrusor contraction at moderate and high concentrations in the study that they conducted to determine the effects of the commonly used anesthetic agents of ketamine, propofol and midazolam on rat detrusor smooth muscle in vitro (Ceran et al 2010 ). Another study investigated the effects of ketamine, propofol, midazolam and ether on cystometric parameters in rats and reported that the urination reflex disappears under ketamine anesthesia while propofol prolongs the urination period but ether inhalation and midazolam make no change in urodynamic parameters (Ozkurkcugil and Ozkan 2010 ).…”
Section: Discussionmentioning
confidence: 99%